ORGANIZATION OF WORKING TIME IN STATE POLICE - Matvejevs, Aleksandrs (Administrative and Criminal Justice, 2015)
Author analyzes the legal regulation of the organization of working time in the State Police of the Republic of Latvia. Author has ascertained problems in legal regulation and made conclusions about current legal situation and provided proposals for improving legal regulation in this area.